Quantitative Techniques / Fifth Edition - Lucey Terry (Letts Educational, 1996)
This text provides a comprehensive understanding of Quantitative Techniques for undergraduate and professional level students. Preface, Introduction to Quantitative Techniques, Probability and Decision Making, Decision Trees, Statistics - Introduction, Statistics - Statistical Inference, Statistics - Hypothesis Testing, Correlation and Regression, Multiple and Non-Linear Regression, Forecasting - Time Series Analysis, Calculus, Inventory Control - Introduction and Terminology, Inventory Control - Types of Control System, Inventory Control - Economic Order Quantity, Inventory Control - Safety Stocks and Reorder Levels, Linear Programming - Introduction, Linear Programming - Graphical Solutions, Linear Programming - Simplex Method for Maximizing, Linear Programming - Simplex Method for Minimizing, Transportation, Assignment, Network Analysis - Introduction and Terminology, Network Analysis - Time Analysis, Network Analysis - Cost Scheduling, Network Analysis - Activity on Nodes, Financial Mathematics, Investment Appraisal - Background and Techniques, Matrix Algebra, Replacement Analysis, Index.